Answer: a=-0.75
Step-by-step explanation:
14a - (2a +9)=2/3 (12a-18)
14a - 2a -9=2/3 * 6(2a-3)
12a-9=2*6/3 (2a-3)
12a-9=2*2(2a-3)
12a-9=4(2a-3)
12a-9=8a-12
4a-9=-12
4a=-3
a=-3/4
a=-0.75
3 x 4 is equal to 12 I think that’s your answer
Answer:
7
Step-by-step explanation:
Answer:
Either
(approximately
) or
(approximately
.)
Step-by-step explanation:
Let
denote the first term of this geometric series, and let
denote the common ratio of this geometric series.
The first five terms of this series would be:
First equation:
.
Second equation:
.
Rewrite and simplify the first equation.
.
Therefore, the first equation becomes:
..
Similarly, rewrite and simplify the second equation:
.
Therefore, the second equation becomes:
.
Take the quotient between these two equations:
.
Simplify and solve for
:
.
.
Either
or
.
Assume that
. Substitute back to either of the two original equations to show that
.
Calculate the sum of the first five terms:
.
Similarly, assume that
. Substitute back to either of the two original equations to show that
.
Calculate the sum of the first five terms:
.
Answer:
y=6x+21
Step-by-step explanation:
simply 3x2+6x+15